The Role of Bio-Enzymes in Achieving Sustainable Development Goal 6: Enhancing Water Quality and Sanitation - Priya K.T. Padma; Motlagh Amin Hossaini; Swarupa M. Lakshmi (E3S Web of Conferences)
Global water stress levels are rising, with water pollution posing a significant challenge to achieving Sustainable Development Goal 6 (SDG 6). Sustainable management of lakes and other freshwater bodies is crucial for improving water sanitation and cleanliness. Bio-enzymes, non-toxic liquid enzymes, have shown a substantial impact on water quality in polluted lakes, naturally biodegrading organic matter. In this study, bio-enzymes were prepared using vegetable and fruit peels, with fermentation metabolites including carbohydrates, proteins, mineral salts, microbes, and organic acids. The pH of the bio-enzyme was recorded at 3.8, and the digestion period of the water sample was 60 days. Bio-enzyme solutions of 2% and 5% concentrations were applied initially and repeated after 20 days. Samples were analyzed after 20 and 40 days of application. Results showed significant improvements in dissolved oxygen (DO), biological oxygen demand (BOD), and chemical oxygen demand (COD) values, bringing them within permissible limits. The 5% bio-enzyme application proved more effective than 2% in water treatment. Therefore, bio-enzyme application presents an eco-friendly and sustainable method for enhancing water quality, contributing to the achievement of SDG 6 and advancing clean water and sanitation efforts.